Caregiver strategies supporting community participation among children and youth with or at risk for disabilities: a mixed-methods study - Kaelin, Vera C.; Saluja, Shivani; Bosak, Dianna L.; Anaby, Dana; Werler, Martha; Khetani, Mary A. (Frontiers in Pediatrics, 2024)
The purpose of this mixed-methods study was to examine the role of caregiver strategies to support community participation among children and youth with disabilities and those at-risk, from the caregiver perspective. For the quantitative phase, we tested the hypothesized positive effect of participationfocused caregiver strategies on the relationship(s) between participation-related constructs and community participation attendance and involvement. For the qualitative phase, we solicited caregiver perspectives to explain the quantitative findings. Methods: An explanatory sequential mixed-methods design (QUAN>qual) was used. For the quantitative phase, we conducted secondary analyses of data collected during a second follow-up phase of a longitudinal cohort study including 260 families of children and youth (mean age: 13.5 years) with disabilities and those atrisk (i.e., 120 families of children and youth with craniofacial microsomia (CFM); 140 families of children and youth with other types of childhood-onset disabilities). Data were collected through the Participation and Environment Measure -Children and Youth, the Pediatric Quality of Life Inventory, and the Child Behavior Checklist and analyzed using structural equation modeling. For the qualitative phase, we conducted semistructured interviews with 8 caregivers of children and youth with disabilities and those at-risk (i.e., 3 caregivers of children and youth with CFM; 5 caregivers of children and youth with other childhood-onset disabilities). Interviews were transcribed verbatim and inductively content analyzed. Results: Our model reached acceptable to close model fit (CFI = 0.952; RMSEA = 0.068 [90% CI = 0.054-0.082]; SRMR = 0.055; TLI = 0.936), revealing no significant effect of the number of participation-focused caregiver strategies on the relationships between participation-related constructs (e.g., activity competence, environment/context) and community participation in terms of attendance and involvement. Qualitative findings revealed three main categories for how caregivers explained these quantitative results: 1) caregiver workload and supports needed for implementing strategies; 2) caregivers careful strategy quality appraisal; and 3) community setting characteristics hindering successful strategy implementation. Discussion: Findings suggest that the insignificant effect of the number of caregiver strategies may be explained by intensified need for caregiver effort and support to develop and implement quality strategies that are responsive to community setting characteristics.